Shingling Technology For Cell Interconnection: Technological Aspects And Process Integration. (September 2018) - Tonini, D.; Cellere, G.; Bertazzo, M.; Fecchio, A.; Cerasti, L.; Galiazzo, M.
Abstract: Shingling technology is an extremely interesting development of cell interconnection in a photovoltaic module due to higher power densities at the same or lower cost, and increasing availability of suitable Electrically Conductive Adhesives (ECAs) and equipment. The shingling approach provides several advantages compared to standard modules, namely: lower ohmic losses, better area utilization, lower processing temperature, lower operating temperature resulting in enhanced energy yield, improved aesthetics. In this work, we demonstrate the performance gain obtained with shingling interconnection technology in terms of module output power and efficiency. Moreover, we describe the technological challenges for each step in the shingling assembly process flow.